Genotype-by-environment interaction of Solanum quitoense (Lam.) using the AMMI model (2024)
The basis for genetic improvement for the cultivation of lulo (Solanum quitoense Lam.) in Colombia is limited. Research related to genotype-by-environment interaction (GEI) and stability in agronomic traits is scarce. To identify outstanding genotypes, GEI and the stability of fruit weight (FW), ascorbic acid (AA), and yield of 10 half-sib families (HSF) were evaluated. At the locations of San Pedro de Cartago, Arboleda, Tangua and La Union of the department of Nariño (Colombia), four trials were established under the randomised complete block design with four repetitions. To analyse GEI, the additive main effects and multiplicative interaction (AMMI) model and some AMMI stability parameters were used. In yield, the HSF7 and the control presented specific adaptation for Tangua, with 12.82 and 13.41 t ha-1, respectively and FW greater than 100 g. In Arboleda, HSF29 obtained the highest yield (16.14 t ha-1) with an FW of 100.53 g. HSF4, HSF28 and HSF49 reached yields above 9.0 t ha-1 and a FW greater than 100 g; therefore, they are recommended for any of the environments evaluated given their stability. HSF25 in AA and HSF29 in yield presented specific adaptation in Arboleda. Stable families across environments and with good yield were HSF4, HSF28, and HSF49, HSF4 and HSF28 showed higher values in two of the three traits, and HSF49 was outstanding in all three variables. These families can be used in plant breeding programmes as parents or distributed to farmers as improved varieties.